Pengaruh Pertumbuhan Penjualan, Debt to Equity Ratio (Der), Dan Ukuran Perusahaan Terhadap Return on Assets (ROA) Pada PT Indofood Sukses Makmur Tbk Tahun 2016-2024 - Febryan Nurdiani; Kartika Berliani (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Fluctuations in the Return on Assets (ROA) of PT Indofood Sukses Makmur Tbk for the period 2016-2024 show an inconsistent relationship between sales growth, Debt to Equity Ratio (DER), and company size on profitability, particularly in the period 2023-2024 where low sales growth was followed by an increase in ROA. This study aims to analyze the effects of sales growth, DER, and company size on PT Indofood Tbk's ROA for the period 2016-2024, both partially and simultaneously. The research employed a descriptive and verificatory quantitative approach, using quarterly data for the 2016-2024 period, and analyzed the data using multiple linear regression in SPSS version 27. The results show that sales growth has a significant negative effect on ROA (β = -0.123; p = 0.038), indicating that sales expansion without cost efficiency reduces profitability. DER has a significant negative effect on ROA (β = -3.449; p = 0.007), indicating that high leverage erodes net income through higher interest expenses. Company size does not have a significant effect on ROA (β = -0.173; sig = 0.489), indicating that asset expansion does not automatically increase profitability. Simultaneously, all three variables had a significant effect on ROA (F = 6.951; p < 0.001), with an R-squared of 39.5%. This study has practical implications for management, emphasizing the need to focus on operational efficiency, deleveraging strategies, and asset-investment selectivity to improve company profitability